PERUBAHAN IKLIM DAN ADAPTASI KAPITALISME - Maemunah, Siti; Hakim, M.Lukman (Direktorat Jenderal Peraturan Perundang-undang, Kementerian Hukum dan Hak Asasi Manusia, 2009)
The increasing concentration of green house gasses–watervapor, carbondioxide, and methane–in the atmosphere trappedsun’s heat and warming up the earth. This phenomenon hasbeen going on for years, also known as Global Warming, thateventually causing climate change. In order to respond thisanthropogenic climate change, countries ratifying the KyotoProtocol are endorsing conservation and forest security tobalance carbon emission, later known as part of CleanDevelopment Mechanism project. The last forests in SouthernCountries are certified and the credits then can be traded bycompanies in developed countries, the highest green housegasses emitters. By participating in foreign CDM projects, thesedeveloped countries already considered carbon-neutral for theiremission. Lately, Carbon Credit mechanism dominates thediscussion of pursuing Kyoto Protocol’s target which to reducethe world emission by 5% in 2012. Through this system, theAnnex 1 countries should pay 100 to 500 million dollar US perone million hectare of forest annually. Nevertheless, in closerobservation it revealed that the Carbon Credit presents assmokescreen to alter the primary issue that causing climatechange, failure in global development model and to elude takingresponsibility in global climate change impact management.Therefore, there has been no attempt in shifting lifestyle toreduce the consumption of fossil-based energy, both in theAnnex 1 or non-Annex 1 countries. Instead, the consumptionof fossil-based energy has continuously increasing worldwide.In Indonesia, forest clearing keep happening along with theincreasing rate of mining excavation and coal export especiallyto Annex 1 countries.